Protein factors involved in the assembly of very low density lipoproteins - Links, Philip Harold (University of Ottawa (Canada), 2005)
Genetic data have suggested a correlation between apolipoprotein C-III (apoC-III) and familial combined hyperlipidemia (FCHL). This observation has been confirmed by clinical data that show an elevation of circulating apoC-III in FCHL patients. Yet the underlying mechanism for the hyperlipidemic effect of apoC-III remains unclear. We postulate that an elevation of apoC-III expression might be associated with enhanced hepatic very low density lipoprotein (VLDL) secretion. To test this hypothesis, human apoC-III cDNA was transfected into McA-RH7777 rat hepatoma cells, that lacked endogenous apoC-III protein; triacylglycerol (TG) apolipoprotein B and VLDL secretion was determined. In transient (p<.0005) and stable transfectants (p<.0008), expression of recombinant apoC-III led to a two-fold increase in 3H-TG secretion only in the presence of 0.4 mM exogenous oleate (OA). This increased 3H-TG secretion was specifically associated with the VLDL1 sub fraction ( Sf) > 100. ApoB-100 in the VLDL1 sub fraction also increased with apoC-III expression. I postulated that structural determinants shared by the other apoC proteins, apoC-I and apoC-II may also lead to an increase in VLDLI. Stable cell lines expressing apoC-I and apoC-II also stimulated 3H-TG secretion as well as apoB100 in the VLDL 1 fraction. Thus, hepatic apoC levels increase VLDL1 secretion particularly in the presence of OA. Finally I attempted to identify a novel TG synthetic enzyme, phosphatidate phosphohydrolase (PAP-1). This enzyme activity hydrolyzes the phosphate group of phosphatidic acid to produce diacylglycerol (DG) for TG production. Since limiting TG levels lead to apolipoprotein B-100 degradation and aborted lipoprotein synthesis I postulate that PAP-1 may be involved in lipoprotein assembly and secretion. This research addresses two accessory protein factors apoC-III and PAP-1, involved in lipid mobilization for TG rich lipoprotein assembly and secretion.
Keywords: Chemistry, Biochemistry.